Results of myxomycete experiments could be affected by temperature in standard laboratory conditions - Rojas Alvarado, Carlos Alonso (2023)
Moist chamber cultures are valuable for myxomycete research and can be used for the analysis of ecological patterns with implications in ecosystem conservation programs. However, to make comparisons between datasets valid, the method should be redesigned considering potential biases affecting the generation of results. In the present study, both the effect of the general climate of the laboratory and two microclimatic variables within the moist chamber were studied in relation with the obtained data. Of all the recorded variables, temperature was observed to affect the results, both at the level of the general laboratory climate and in relation with the microclimate of the moist chamber. Increments in laboratory and moist chamber temperature increased the probability, three or fourfold, associated with a higher number of records or species within a group of equivalent samples. Such probabilistic differences are significant enough to suggest that using the moist chamber technique in “standard” laboratory conditions is not enough for cross-dataset comparisons that increase the potential of myxomycete data for applications outside of the biological sciences.